THE STUDY OF UNDESIRABLE SOCIAL SKILLS OF STUDENTS AND THEIR RELATIONSHIP WITH ACADEMIC PERFORMANCE - Dr. Muhammad Tahir Nadeem; Marrium Ishtiaq; Nosheen Malik (International Journal of Contemporary Issues in Social Sciences, 2024)
Social skills are key in increasing academic outcomes and students' learning at college levels. Social skills help students to communicate, cooperate, and adjust themselves with their fellow students and this collaboration allows them to achieve their academic goals. Undesired social skills, on the contrary, affect the social adjustment of the students as well as the academic achievement in the class. The current study focused on the analysis of the undesired social skills of students and the relationship of these skills with the academic performance of the students. The objectives of this study were to examine various undesired social skills and to discover their relationship with the academic performance of students. A questionnaire was used to collect quantitative statistics to probe the issue under study. The study population consisted of teachers from private and public sector colleges in Bahawalpur Division. A systematic random sampling technique was used and the study sample was 190. The data were analyzed by using the software SPSS, (Statistical Packages for Social Sciences), and mean, frequencies, percentages, and standard deviation were derived. The results of the study revealed that the majority of the high achiever students did not possess most of the undesired social skills as well as, respondents agreed that the majority of the low academic achievers possess few of the listed undesired social skills. It was concluded that most of the students who show aggressive behaviors, also fall in the category of low academic achievers. Moreover, undesired social skills negatively affect the academic outcomes.